Consensus standards of healthcare for adults and children with inflammatory bowel disease in the UK. Issue 3 (24th July 2019) - Kapasi, Rukshana; Glatter, Jackie; Lamb, Christopher A; Acheson, Austin G; Andrews, Charles; Arnott, Ian D; Barrett, Kevin J; Bell, Graham; Bhatnagar, Guaraang; Bloom, Stuart; Brookes, Matthew James; Brown, Steven R; et al.
Abstract : Objective: Symptoms and clinical course during inflammatory bowel disease (IBD) vary among individuals. Personalised care is therefore essential to effective management, delivered by a strong patient-centred multidisciplinary team, working within a well-designed service. This study aimed to fully rewrite the UK Standards for the healthcare of adults and children with IBD, and to develop an IBD Service Benchmarking Tool to support current and future personalised care models. Design: Led by IBD UK, a national multidisciplinary alliance of patients and nominated representatives from all major stakeholders in IBD care, Standards requirements were defined by survey data collated from 689 patients and 151 healthcare professionals. Standards were drafted and refined over three rounds of modified electronic-Delphi. Results: Consensus was achieved for 59 Standards covering seven clinical domains; (1) design and delivery of the multidisciplinary IBD service; (2) prediagnostic referral pathways, protocols and timeframes; (3) holistic care of the newly diagnosed patient; (4) flare management to support patient empowerment, self-management and access to specialists where required; (5) surgery including appropriate expertise, preoperative information, psychological support and postoperative care; (6) inpatient medical care delivery (7) and ongoing long-term care in the outpatient department and primary care setting including shared care. Using these patient-centred Standards and informed by the IBD Quality Improvement Project (IBDQIP), this paper presents a national benchmarking framework. Conclusions: The Standards and Benchmarking Tool provide a framework for healthcare providers and patients to rate the quality of their service. This will recognise excellent care, and promote quality improvement, audit and service development in IBD.